Emotional disclosure in palliative care: A scoping review of intervention characteristics and implementation factors. (July 2021) - McInnerney, Daisy; Kupeli, Nuriye; Stone, Paddy; Anantapong, Kanthee; Chan, Justin; Flemming, Kate; Troop, Nicholas; Candy, Bridget
Background: Emotional disclosure is the therapeutic expression of emotion. It holds potential as a means of providing psychological support. However, evidence of its efficacy in palliative settings is mixed. This may be due to variation in intervention characteristics. Aim: To derive a greater understanding of the characteristics of potentially effective emotional disclosure-based interventions in palliative care by: (1) Developing a taxonomy of emotional disclosure-based interventions tested in people with advanced disease and (2) Mapping and linking objectives, outcomes, underlying mechanisms, and implementation factors. Design: A scoping review drawing on Intervention Component Analysis to combine evidence from studies' methods, results, and discussion sections. Data sources: Six databases were searched to May 2020 including CINAHL, PsycINFO, and MEDLINE. Studies of emotional disclosure in adults with advanced disease were included. Study quality was appraised using an established tool. Results: Seven thousand seven hundred ninety-two unique records were screened, of which 25 primary studies were included. Intervention characteristics were grouped into classes within three domains: topic of disclosure, format, and dose. Evidence was not available to determine which, if any, of the characteristics is most effective. Thematic synthesis of evidence from methods and discussion sections identified factors to consider in tailoring an emotional disclosure-based intervention to this setting, including: population characteristics (e.g. time since diagnosis), providing a safe environment, and flexibility in format. Conclusions: This review approach facilitated a clearer understanding of factors that may be key in developing emotional disclosure-based interventions for palliative populations. Intervention Component Analysis has potential for application elsewhere to help develop evidence-based interventions.